The Function of Narrative:: Toward a Narrative Psychology of Meaning - Schiff, Brian (Narrative Matters, 2012)
In this paper, I argue that the most salient aspect of narrative is not the arrangement of speech elements into a particular order but the kinds of actions that can be accomplished with narratives. Narrative is best thought of as a verb, “to narrate,” or the derived form, “narrating.” It is an expressive action, something that persons do. I argue that one of the primary functions of narrating is to “make present” life experience and interpretations of life in a particular time and space. Narrating brings experience and interpretations into play, into a field of action, in a specific here and now.